Singing Pitch Guide for Multiple Voice Pitch Offset Detector - Azizan, Muhammad Hariz; Amirul Syafiq Sadun; Nor Anija Jalaludin (Progress in Engineering Application and Technology, 2022)
Singing is a beautiful piece of art but singing without proper technique can be miserable to hear. A lot of people love to sing but not everyone has good skills to control their voice pitch in singing. Three volunteers who like to sing were inquired to do a test on the system which analyze voice pitch to see whether they will have an improvement after they start using the system. The results obtained shows that the ability of the volunteers to control and produce the right voice pitch are improved. Wider octave detection is recommended for further improvement.